Republic of Zambia Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2018)
Zambia has successfully raised its average annual gross domestic product (GDP) growth rate since the early 2000s. Between 2004 and 2014, it averaged 7.4 percent per year. This success was driven by an improvement in the macroeconomic indicators (relative to the 1980s and 1990s), debt relief, heavy investment in the social sectors (by the government and cooperating partners), and a large increase in mining and agricultural production since 2004. This success raised average p Rapid urbanization has been accompanied by a decrease in urban poverty incidence, but masks sluggish growth in small towns and cities. After a decade of de-urbanization in the 1990s, urbanization has been an important driver of change over the past 15 years. However, from 2000 to 2014, urban growth in Zambia has been significantly more focused on the capital city than the average for Sub-Saharan Africa. The annual population growth of Lusaka is over twice the average for Sub-Saharan Africa (1 percent). In contrast, the share of secondary towns in Zambia is growing more slowly than in the rest of Africa (by only 0.7 percent in Zambia compared with 1.8 percent elsewhere). These disparities may exacerbate uneven territorial development, as small towns and cities play a crucial role in strengthening the links among firms; between firms and consumers; and within local, provincial, national, and international supply chains. er capita incomes after decades of economic volatility since the country’s independence in 1964. The current development model being pursued has imposed environmental and resource liabilities. Agricultural growth has been based on increasing land use rather than improved productivity, leading to rapid deforestation. Mining activities have resulted in pollution, and Zambia also faces high and growing climate change impacts. Copper price volatility also continues to challenge macroeconomic and fiscal management. Debt levels have soared to risky levels only 12 years after the Heavily Indebted Poor Country (HIPC) and the Multilateral Debt Relief Initiative (MDRI) programs provided US$6.5 billion of debt relief from 2005.